Long-Term Spatiotemporal Changes in Endemic Threshold Populations in England and Wales – A Multi-Disease Study - Munro, Alastair (2021)
Metapopulation dynamics play a critical role in driving endemic persistence and transmission of childhood infections. The endemic threshold is defined as the minimum population size required to sustain a continuous chain of infection transmission. The concept is fundamental to the implementation of effective vaccine-based disease control programmes. Vaccination serves to increase endemic threshold population size, promoting disease fadeout and eventual elimination of infection. To date, empirical geographical investigations of endemic threshold populations have tended to focus on isolated populations in island communities. Few studies have examined endemic threshold dynamics in ‘mainland’ regional populations with divergent spatial structures and varying levels of connectivity between subpopulations.